Effect of Neem Leaf Extract on Reproductive Potential of Male Rats Fed High-Fat Diet - Nur Laila; Agung Janika Sitasiwi; Sri Isdadiyanto (Biosaintifika: Journal of Biology & Biology Education, 2022)
Neem leaves contain bioactive compounds, including tannins, saponins, flavonoids, alkaloids, and terpenoids which are thought to have a cholesterol-lowering effect, but are also accompanied by antifertility effects. This study aims to determine the effect of neem leaf ethanol extract on the structure and reproduction of hyper-cholesterol or hyperlipidaemic male rats. The study used a completely randomized design which was divided into 6 groups with 4 repetitions, namely: P0 (negative control), P1 (positive control), P2 (8 mg/gBW simvastatin), P3, P4, and P5 (75, 100, and 125 mg/gBWof neem leaf extract). Parameters observed were testicular structure (epithelial thickness and seminiferous tubule diameter), GSI, ESI, epididymal protein expression and concentration, morphology and number of spermatozoa. Exposure to ethanolic extract of neem leaves had a significant effect on seminiferous tubule diameter, morphology and number of spermatozoa in white rats fed a high-fat diet, but did not differ significantly on the thickness of the seminiferous tubule epithelium and GSI, so it can be concluded that the effect of ethanolic extract of neem leaves in hypercholesterolemic rats decreased the structure and function of male reproduction as indicated by spermatozoa morphology, spermatozoa number, epididymal protein expression, and testicular structure, supported by the results of protein concentration, GSI, and ESI.